2019
DOI: 10.1155/2019/1038069
|View full text |Cite
|
Sign up to set email alerts
|

GTSE1, CDC20, PCNA, and MCM6 Synergistically Affect Regulations in Cell Cycle and Indicate Poor Prognosis in Liver Cancer

Abstract: GTSE1 is well correlated with tumor progression; however, little is known regarding its role in liver cancer prognosis. By analyzing the hepatocellular carcinoma (HCC) datasets in GEO and TCGA databases, we showed that high expression of GTSE1 was correlated with advanced pathologic stage and poor prognosis of HCC patients. To investigate underlying molecular mechanism, we generated GTSE1 knockdown HCC cell line and explored the effects of GTSE1 deficiency in cell growth. Between GTSE1 knockdown and wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
(49 reference statements)
2
16
0
Order By: Relevance
“…Proliferating cell nuclear antigen (PCNA) plays critical roles in many aspects of DNA replication and replication-associated processes, including translesion synthesis, error-free damage bypass, break-induced replication, mismatch repair, and chromatin assembly 48 . Zheng et al analyzed HCC data sets in GEO and TCGA and found that PCNA might be promising prognostic biomarker for HCC 49 . Nucleolar KKE/D repeat proteins NOP56p and NOP58p interact with NOP1p and are required for ribosome biogenesis 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Proliferating cell nuclear antigen (PCNA) plays critical roles in many aspects of DNA replication and replication-associated processes, including translesion synthesis, error-free damage bypass, break-induced replication, mismatch repair, and chromatin assembly 48 . Zheng et al analyzed HCC data sets in GEO and TCGA and found that PCNA might be promising prognostic biomarker for HCC 49 . Nucleolar KKE/D repeat proteins NOP56p and NOP58p interact with NOP1p and are required for ribosome biogenesis 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Its common molecular function is to bind to the tumor suppressor protein p53 and impede the cancer suppressor ability of p53 in cancers [ 8 ]. Some studies further reported that upregulation of GTSE1 was frequently found in several types of human cancers [ 9 , 10 ]. Upregulation of GTSE1 promoted cell proliferation and cell migration and invasion in the progress of hepatocellular carcinoma [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 GTSE1 regulates p53 by stimulating the relocalization of p53 to the cytoplasm, subsequently inhibiting p53-induced apoptosis. 27 The overexpression of GTSE1 has been reported to be involved in the progression of many cancers, such as gastric cancer, 8 breast cancer, 28 liver cancer, 29 non-small-cell lung cancer, 9 acral melanoma 7 and bladder cancer. 30 However, the role and underlying molecular mechanism of GTSE1 in PCa remain unknown.…”
Section: Discussionmentioning
confidence: 99%